Some relationships between the geometry of the tangent bundle and the geometry of the Riemannian base manifold - Henry, Guillermo Sebastian (2012)
We compute the curvature tensor of the tangent bundle of a Riemannian manifold endowed with a natural metric and we get some relationships between the geometry of the base manifold and the geometry of the tangent bundle.